KREATIVITAS BARTENDER SEBAGAI UPAYA MENINGKATKAN PENJUALAN MINUMAN DI INTERCONTINENTAL BALI RESORT - Dewa Ayu Diyah Sri Widari¹; Luh Kompiang Sari (Journal of Tourism and Interdiciplinary Studies, 2023)
Creativity plays an important role in determining victory in business competition. The existence of bartenders is a vital thing in bar operations, on the other hand, the quality of the products sold also plays an important role. This study aims to examine the creativity of bartenders in an effort to increase beverage sales at InterContinental Bali Resort and to examine the problems faced by bartenders in creating to increase beverage sales. This study used qualitative descriptive research method. Data collection techniques used are observation, interviews and documentation. The results showed that the creativity of a bartender has a large share in the sale of drinks in the bar and is the main capital of a bartender. Various creativity is carried out by bartenders as an effort to increase beverage sales by creating special menus, serving drinks to appeal to guests' tastes, displaying juggling attractions, mastering mixology, and promoting favorite menus for guests visiting the bar. Bartenders in making efforts to increase beverage sales, face various problems that can affect bar operations.